Quasi-Synchronization of Nonidentical Fractional-Order Memristive Neural Networks via Impulsive Control - Ruihan Chen; Tianfeng Zhao (Discrete Dynamics in Nature and Society)
This paper investigates the quasi-synchronization of nonidentical fractional-order memristive neural networks (FMNNs) via impulsive control. Based on a newly provided fractional-order impulsive systems comparison lemma, the average impulsive interval definition, and the Laplace transform, some quasi-synchronization conditions are obtained with fractional order 0<α<1. In addition, the error convergence rates and error boundary are also obtained. Finally, one simulation example is presented to show the validity of our results.